2014
DOI: 10.1007/978-3-319-14484-9_7
|View full text |Cite
|
Sign up to set email alerts
|

The AORTA Architecture: Integrating Organizational Reasoning in Jason

Abstract: Abstract. Open systems are characterized by a diversity of heterogeneous and autonomous agents that act according to private goals, and with a behavior that is hard to predict. They can be regulated through organizations similar to human organizations, which regulate the agents' behavior space and describe the expected behavior of the agents. Agents need to be able to reason about the regulations, so that they can act within the expected boundaries and work towards the objectives of the organization. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…As mentioned, we have implemented an earlier version of the framework in Java and have integrated it with the Jason platform [30]. We plan to extend that work with the complete and updated operational semantics presented in this paper.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned, we have implemented an earlier version of the framework in Java and have integrated it with the Jason platform [30]. We plan to extend that work with the complete and updated operational semantics presented in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…Given that our component is designed to be independent from the cognitive agent, we need to ensure 1) that changing the agent's beliefs (or goals) does not create inconsistencies in the agent's reasoning and 2) that the agent's beliefs (or goals) used in the organizational reasoning does not change during the organizational reasoning phases. In [30], we showed that both of these issues could be addressed by executing the AORTA reasoning cycle and the cognitive agent's reasoning cycle sequentially. Since the two cycles are not executed in parallel, changes to the agent's beliefs, goals or organizational beliefs will only be used (and altered) by a single process.…”
Section: The Aorta Reasoning Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…MOISE+ is an organization meta-model which has been implemented in the Jason agent programming platform [10,11]. In contrast we use AORTA, which has also been implemented in Jason [12], and GAMA, which is an agent-based simulation platform. There are also other methods to include normative reasoning in agents which do not incorporate an organization meta-model [13][14][15].…”
Section: Related Workmentioning
confidence: 99%